Sistem Informasi Penjualan (E-Commerce) UMKM DANISA Collection - Alfath Nafidz Albalkhi; Rita Komalasari (SisInfo, 2024)
Information technology has been implemented in almost all fields and can have a positive impact on many variables. Its implementation in sales can support performance and competitiveness, which is directly related to profits. Companies need to develop conventional systems into information systems to present real-time information. Online trading has become a popular trend in recent years due to its ability to reach the target market more effectively than offline trading. DANISA Collection is a business that provides various kinds of clothing. The current sales system and data processing of goods are still done conventionally. This can cause obstacles if buyers cannot visit the store directly because currently orders are made through conversations via WhatsApp or in-store. To overcome this problem, there is a need to migrate the conventional data management system to a website-based sales information system. The purpose of this research is to help MSMEs to increase sales efficiency. This research uses the SDLC Waterfall model, which is referred to as the linear sequential or classical life flow model, offering a structured approach to software development. The result of this research is DANISA Collection implements a website-based sales information system, this system has been tested which results in all functioning properly.